(3GSJbUGA GdfXQ aj GdbVGA hGdbOQs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3gPg GdQSGdI GdehSheI HESJbUGA GdfXQ aj GdHMK Yf GdbVGA hGdbOQ GdoeTJedI Ydi MLL GdaQjbjf hCOdI GdNUejf s
(3BNQgG (B:s
(3aEf GdSdWGf EPG CeQ hRjQg Cf jaUd aUdkG jchf GdhRjQ ajg oeNJGQkG hdjcf gPG BNQ eG fhQOg aj gPG GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B72s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds